PENANGANAN STUNTING DALAM PERSPEKTIF MODEL KEBIJAKAN KONVERGENSI DI KABUPATEN LOMBOK TIMUR - KABUL, LALU MUH. (GANEC SWARA, 2023)
A new model which implemented to handle stunting called convergence policy model. The aim of the study is to analysis the convergence policy model.  The study method used is mixed methods, namely quantitative and qualitative. The result of study showed that convergence policy model which is recently implemented (“existing model”) consist of 8 integrated action where responsibility of each action is organization/agencies at regency level. In order to accelerate increasing of stunting prevalency, the “existing model” need to improve tobe a “recommended model” which consist of 9 integrated action where responsibility of each action is not only organization/agencies at regency level, but also village government.